Gastroesophageal reflux disease and dental erosion: The role of bile acids. (July 2022) - Milani, Daiane Cristina; Borba, Márcia; Farré, Ricard; Grando, Luciana Grazziotin Rossatto; Bertol, Charise; Fornari, Fernando
Abstract: Objectives: To identify the bile acids in the saliva of patients with and without gastroesophageal reflux disease (GERD), and evaluate their effect on tooth surface. Design: A cross-sectional study involved 26 GERD patients and 40 controls without GERD. Dental erosions were identified, saliva was collected and analyzed with chromatography for bile acid identification. An in vitro study assessed the effect of enamel exposition to taurocholic acid in concentrations of 1 µM, 10 µM, and a mixture of taurocholic acid and glycocholic acid at 10 µM on enamel microhardness, calcium release, and surface topography. Results: Salivary bile acids were analyzed from 22 GERD patients and 40 controls. All these participants presented taurocholic acid and glycocholic acid in the saliva. The salivary amount of taurocholic acid was greater than glycocholic acid in both GERD patients (area under the curve: 7946 vs. 1361; p < 0.001) and controls (10, 815 vs. 1290; p < 0.001). The salivary amount of taurocholic acid was greater in controls than in GERD patients (10, 815 vs. 7946; p < 0.001). Dental erosion was more prevalent in GERD patients than in controls (27% vs. 7%; p = 0.041). In the GERD presence, the amount of glycocholic acid was greater in patients with dental erosion (1777 vs. 1239; p = 0.041). Enamel exposed to taurocholic acid at 10 µM, combined or not with glycocholic acid, had their microhardness increased, accompanied by calcium release, with no changes in surface topography. Conclusions: Taurocholic acid was the predominant salivary bile acid, particularly in controls without GERD. This bile acid had no deleterious effect on the enamel structure. Highlights: Dental erosion has an established cause with gastroesophageal reflux disease. The main bile acids found in saliva were taurocholic and glycocholic. The taurocholic acid was prevalent in both studied groups. Saliva of patients with reflux and erosion had greater amount of glycocholic acid. Bile acids had no deleterious effect on the enamel structure.